Alimentação escolar e alimentos da agricultura familiar em Região Metropolitana Amazônica Brasileira - Riziane Duarte Portal; Ima Célia Guimarães Vieira; Otávio do Canto (Confins)
The National School Feeding Program (PNAE) – the largest and oldest public policy in the area of ​​food and nutrition in Brazil, constituting a Food and Nutritional Security (SAN) strategy – aims to promote and guarantee access to adequate food for basic education students. Federal Law No. 11,947/2009 links the PNAE to Family Farming, determining that a minimum percentage of 30% of the financial resources transferred by the Union be allocated to the purchase of food from this productive category. This work analysed the process of purchasing food from family farming to supply school meals in the Federal Institutions of Higher Education (IFES) in the Metropolitan Region of Belém (RMB) as an instrument for local development and for SAN. This is a descriptive study with a qualitative approach of a theoretical-empirical nature, for which semi-structured interviews were carried out with employees involved in the purchasing process of the PNAE in these Institutions, the data were evaluated through content analysis. It was found that the organization of the PNAE in the IFES of the RMB complies with Law nº 11.947/2009, regarding the acquisition of foodstuffs from family farming. However, this acquisition is recent, it has shown important advances, although limiting factors are still present, such as the limited variety of foods, the still limited knowledge of the actors involved in the purchase process about the legislation and norms that regulate the supply of food for the PNAE. It is necessary to improve the program to the specificities of the IFES in order to improve the purchasing process of family farming, contributing to local development and SAN.